TREN DAN TRANSFORMASI ELECTRONIC WORD OF MOUTH DALAM LIMA TAHUN TERAKHIR: KAJIAN SISTEMATIS PERKEMBANGAN STRATEGI DAN PENGARUHNYA PASCA PANDEMI COVID-19 - Wibowo, Yohanes Gunawan (Universitas Muhammadiyah Bengkulu, 2025)
The rapid development of digital technology and shifting consumer behavior in the post-COVID-19 era have driven a major transformation in marketing communication patterns, particularly through Electronic Word of Mouth (e-WOM). Over the past five years, e- WOM has evolved beyond simple text-based reviews to become visual and interactive content disseminated via social media platforms such as TikTok, Instagram, and YouTube. This study aims to regularly examine the trends and transformations of e-WOM in terms of format, distribution channels, adaptive strategies used by businesses, and its impact on consumer behavior in the digital landscape after the pandemic. The research employs a Systematic Literature Review (SLR) method by analyzing 18 scholarly articles sourced from reputable databases such as Scopus, ScienceDirect, and Google Scholar, selected based on keywords: “electronic word of mouth,” “e-WOM,” “post-pandemic digital marketing,” and “consumer behavior.” The findings reveal that e- WOM has become a strategic instrument that not only enhances brand credibility through authentic and emotional content but also serves as a core component of data-driven, community-oriented, and participatory digital marketing strategies. This study provides valuable insight into the dynamics of digital consumer communication and offers practical guidance for companies and MSMEs in managing e-WOM effectively